Prototyping of User Interfaces for Mobile Applications - Bähr, Benjamin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book investigates processes for the prototyping of user interfaces for mobile apps, and describes the development of new concepts and tools that can improve the prototype driven app development in the early stages. It presents the development and evaluation of a new requirements catalogue for prototyping mobile app tools that identifies the most important criteria such tools should meet at different prototype-development stages. This catalogue is not just a good point of orientation for designing new prototyping approaches, but also provides a set of metrics for a comparing the performance of alternative prototyping tools. In addition, the book discusses the development of Blended Prototyping, a new approach for prototyping user interfaces for mobile applications in the early and middle development stages, and presents the results of an evaluation of its performance, showing that it provides a tool for teamwork-oriented, creative prototyping of mobile apps in the early design stages.
Introduction -- State of Prototyping Mobile Application User-Interfaces -- Prototyping Requirements -- Blended Prototyping - Design and Implementation -- Comparative Evaluation of Blended Prototyping -- Conclusion.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Telecommunication; User Interfaces and Human Computer Interaction; Communications Engineering, Networks